Pharmacokinetic Similarity of ABP 654, an Ustekinumab Biosimilar Candidate: Results from a Randomized, Double‐blind Study in Healthy Subjects - Chow, Vincent; Mytych, Daniel T.; Das, Shyamal; Franklin, Janet (Clinical pharmacology in drug development, 2023)
ABP 654 is a proposed biosimilar to ustekinumab reference product (RP) which works through antagonism of interleukin‐12 and interleukin‐23. Ustekinumab RP is used for the treatment of chronic inflammatory conditions, including some forms of plaque psoriasis, psoriatic arthritis, Crohn's disease, and ulcerative colitis. A randomized, double‐blinded, single‐dose, 3‐arm, parallel‐group study was conducted to assess the pharmacokinetic (PK) similarity of ABP 654 with ustekinumab RP sourced from the United States (US) and the European Union (EU); the PK similarity of ustekinumab US versus ustekinumab EU; and the comparative safety, tolerability, and immunogenicity of all 3 products. A total of 238 healthy subjects were randomized 1:1:1 and stratified by gender and ethnicity (Japanese versus non‐Japanese) to receive a single 90 mg subcutaneous injection of ABP 654 or ustekinumab US or ustekinumab EU. PK similarity was established based on 90% confidence intervals (CIs) for the primary endpoints of area under the concentration‐time curve from time 0 extrapolated to infinity (AUCinf) and maximum observed serum concentration (Cmax) being contained within the prespecified margin of 0.8–1.25. No clinically meaningful differences in immunogenicity were found among the 3 products. Adverse events were similar between treatment groups and consistent with the safety profile of ustekinumab RP. Results indicate that ABP 654, ustekinumab US and ustekinumab EU share similar PK and safety profiles.